The looks of a winner: beauty, gender, and electoral success - Niclas Berggren; Henrik Jordahl; Panu Poutvaara (Center for Economic Studies and ifo Institute (CESifo), 2007)
We study the role of beauty in politics using candidate photos that figured prominently in electoral campaigns. Our investigation is based on visual assessments of 1,929 Finnish political candidates from 10,011 respondents (of which 3,708 were Finnish). An increase in beauty by one standard deviation is associated with an increase of 1720 percent in the number of votes for the average non-incumbent candidate. The relationship is virtually always statistically significant for female candidates, and in most specifications also for male candidates.
Keywords: D72; J45; J7; 330; Ästhetik; Geschlecht; Politiker; Wahlverhalten; Finnland